Apakah Economic Complexity dan Institusi yang Kuat Mempengaruhi Income Inequality - Rudy Hendra Prasetiya (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2021)
This study investigates the relationship of a country's sophisticated products and institutional indicators on income inequality. Cross-country OLS and fixed-effects estimate regression analysis show that countries with productive economic structures have less inequality. Meanwhile, three government indicators in accountability, political stability, and the rule of law show mixed results. Using the system generalized method of moments (GMM) to control endogeneity, we find evidence of a causal link from economic complexity to income inequality in the short run. Meanwhile, the government's political stability is not a significant predictor.